2020
DOI: 10.3389/fneur.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Controlled Decompression for Severe Traumatic Brain Injury: A Randomized, Controlled Trial

Abstract: Background: Experimental evidence has indicated the benefits of intraoperative controlled decompression for the treatment of severe traumatic brain injury (sTBI). Intraoperative rapid decompression (conventional decompression) for the treatment of sTBI may result in intra-and post-operative complications. Controlled decompression may reduce these complications. Previous clinical trials in China have not yielded conclusive results regarding controlled decompression for sTBI. Therefore, we explored whether contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The incidence of TBI is increasing rapidly due to the significant increase in road traffic collisions, including motor vehicle accidents ( 5 ). Although an increasing number of randomized controlled trials including intracranial pressure monitoring, therapeutic hypothermia, surgical methods and drug administration have been performed in recent years and the long-term outcome has substantially improved, a significant benefit is not observed following drug interventions ( 4 10 ). Hence, studies aiming to further clarify the pathophysiological mechanisms of TBI and search for new and effective pharmacological intervention targets are important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of TBI is increasing rapidly due to the significant increase in road traffic collisions, including motor vehicle accidents ( 5 ). Although an increasing number of randomized controlled trials including intracranial pressure monitoring, therapeutic hypothermia, surgical methods and drug administration have been performed in recent years and the long-term outcome has substantially improved, a significant benefit is not observed following drug interventions ( 4 10 ). Hence, studies aiming to further clarify the pathophysiological mechanisms of TBI and search for new and effective pharmacological intervention targets are important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled decompression technology can protect nerve cells and function by reducing ischemia-reperfusion damage and maintaining vascular regulation. This clinical study also demonstrated that the 6-months outcomes, the incidence rates of intraoperative acute brain swelling, and delayed intracranial hematoma were significantly better in sTBI patients who underwent controlled decompression than in those who underwent rapid decompression 9 . Rapid craniotomy (opening the skull and dura quickly, without controlled ICP release) causes large amounts of arterial blood to pour quickly into the brain tissue, but without appropriate venous outflow, then lead to brain edema and brain swelling.…”
Section: Discussionmentioning
confidence: 53%
“…These experimental results undoubtedly confirmed that controlled decompression can effectively reduce ICP and inhibit the necroptosis pathway as well. Besides, previous clinical trials also improved surgical patient prognosis and decreased the incidences of postoperative complications 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DC a life-saving procedure for treatment of refractory raised ICP, in cases of large hemispheric infarction or significant head injury. [ 4 , 6 ] The benefits of aggressive decompression in the context of TBI and malignant supratentorial infarction have been demonstrated,[ 7 ] where the timing to surgical decompression is debated. [ 9 ] Delayed subdural hematoma and intraoperative brain swelling are recognized complications of decompressive surgery;[ 12 ] however, malignant MCA infarction following craniotomy for subacute SDH has not been reported.…”
Section: Discussionmentioning
confidence: 99%